utilising a Massive Open Online Course (MOOC): a narrative inquiry on the experiences of caregivers in special care centres with online professional development - Samuels, Chantal (Division of Disability Studies, 2025)
In South Africa in 2010, the High Court affirmed the right to education for children with severe to profound intellectual disabilities (SPID). Prior to this judgment, these children were considered ineducable and did not have access to education. Consequently, caregivers were often unprepared to shift from a social welfare care model to educational provision due to their limited training opportunities. This study examines experiences of caregivers with online professional development in the provision of education in care environments in the South African context. Methods: This study utilised a narrative inquiry approach to explore and describe caregivers' experiences of engaging in the Severe to Profound Intellectual Disability Massive Open Online Course (SPID MOOC). The Ethics of care framework was identified as a valuable framework for examining development practices and processes, therefore considered suitable as a framework for exploring the care practices and professionald development of caregivers of learners with SPID at Special Care Centres (SCCs). Purposive sampling was used to select three caregivers from special care centres and protective workshops. The Single Question aimed at Inducing Narrative was employed for data collection. Data were analysed both deductively and inductively. The Ethics of care framework comprising of four phases - Attentiveness, Responsibility, Competence, and Responsiveness - guided the deductive analysis, while subthemes were identified inductively. Results: The findings revealed that participants demonstrated a significant gain in knowledge, skills and positive attitudes through the online course. Four predetermined themes emerged through the phases of the Ethics of care framework: Attentiveness, Responsibility, Competence, and Responsiveness. The study highlights how the online course strengthened caregivers' resilience and creativity in facilitating education and care within resource-constrained environments with insufficient support from the state and community. Caregivers attributed their professional and personal development to their participation in the online course. Conclusion: While caregivers found the online course beneficial to their professional development, it presented certain challenges for other caregivers. Caregivers had context-specific concerns that would affect the participation of those in rural areas, particularly informal caregivers. Their main concerns included limited language options tailored to the South African context, varying levels of computer literacy, device accessibility, and internet connectivity. While these concerns are not exclusive to the South African context, it affects those most in need of training and professional development options.